Testing of mechanisms of action of rituximab and clinical results in high-risk patients with aggressive CD20+ lymphoma - Jezeršek Novaković, Barbara (Radiology and oncology (Ljubljana), 2007)
Background. Rituximab has been applied successfully in the treatment of indolent and aggressive CD20 positive B cell lymphomas, yet the exact in vivo mechanisms of its action have not been unambiguously explained. This study wastherefore aimed to confirm the presumed major mechanisms of action of rituximab and concomitantly to assess the effectiveness of first-line chemoimmunotherapy in high-risk patients with aggressive CD20 lymphomas. Patients, materials and methods. The activity of rituximab was tested in vitroon Raji and SU-DHL-4 cells using the cell proliferation assay and flow cytometry. In the clinical part of the study, 20 high-risk patients with aggressive CD 20 lymphomas were treated with R-CHOP. Results. Only complement-mediated cytotoxicity was observed under the in vitro applied experimental conditions. Neither the direct apoptotic effect nor the antibody-dependent cell-mediated cytotoxicity was detected probably due to a too low concentration of rituximab and a too low ratio of cytotoxic lymphocytes to tumor cells. The treatment outcome in patients was excellent since complete remissions were achieved in 90% of poor-risk patients at the end of primary treatment and 80% of patients were disease free at 18.5 months median observation period. Conclusions. According to our results, the complement-dependent cytotoxicity is an important mechanism of rituximab action in vitro. To achieve direct apoptosis, higher concentrations than 20 micro g/ml of rituximab should be used, while for an effective antibody-dependent cell-mediated cytotoxicity, the ratio of cytotoxic lymphocytes to tumor cells should be higher than 1:1. In the high- risk patients with aggressive CD20 lymphomas, the addition of rituximab to CHOP substantially improves the therapeutic results.
Keywords: Antibodies, Monoclonal; antigeni; Antigeni, CD20; Antigens, Cd20; Apoptosis; Apoptoza; biokemija; Brez bolezni, preživetje; Celica, preživetje; Cell Survival; Disease-Free Survival; Drug Effects; Drug Therapy; Flow Cytometry; limfom; Limfom B-celični; Lymphoma, B-Cell; Monociti; Monocytes; onkologija; Pretočna citometrija; Protitelesa monoklonska; therapy; zdravljenje